PENGEMBANGAN BAHAN AJAR MOTORIK BERBASIS E-LEARNING PADA MATAKULIAH PEMBELAJARAN MOTORIK MAHASISWA S1 PENDIDIKAN JASMANI KESEHATAN DAN REKREASI - Ratno Susanto (Cahaya Ilmu Bangsa Institute, 2024)
In order to improve student motivation and learning outcomes at Nusa Cendana University's Physical Education, Health, and Recreation Study Program, this research aims to produce e-learning-based teaching materials for fundamental tennis techniques, tactics, and strategies. This research and development model applies the 4 D model (Define, Design, Develop, and Dessiminate) in conjunction with the Research and Development (R&D) technique. The rationale behind choosing this development approach is twofold: 1) it involves ongoing revision (evaluation) at every milestone reached in order to generate better instructional materials; and 2) despite the paradigm's simplicity, its use is methodical. methods for gathering data that are utilized to process and analyze review results and product trials for educational materials are methods of both quantitative and qualitative examination. based on validation findings from small group trials, media experts, and material experts. With an average feasibility score of 96.17%, the creation of E-Learning media-based textbooks is deemed